Environmental, public health, and economic development perspectives at a Superfund site: A Q methodology approach. (1st February 2021) - Cooper, Courtney M.; Wardropper, Chloe B.
Abstract: Environmental remediation and restoration at hazardous waste sites is important for reducing risks and sustaining local economies. Navigating trade-offs between diverse and conflicting stakeholder perspectives to identify practical and affordable ways forward is important for sustaining objectives and goals. Differences in stakeholder perspectives are informed by their affiliations and roles and their views towards environmental, economic development, and public health issues. We used Q methodology, an approach that combines priority sorting and interviews, to elicit and interpret the perspectives of 28 stakeholders, representing government entities, non-profits, and industries at a mining-impacted Superfund site in the Coeur d'Alene Basin of Idaho, USA. Four primary perspectives were distinguished by their prioritization of: 1) government intervention, 2) the Superfund remediation, 3) local concerns, and 4) public-private partnerships. Participants' roles and affiliations played an influential role in informing primary perspectives. Overall, collaboration was viewed more favorably when it was associated with concrete implementation pathways. Highlights: Study participants clustered between four primary perspectives. Participants' affiliations and roles strongly influenced the four perspectives. Reciprocal knowledge exchange may inform perspectives influence by core issues. Tangible pathways for implementation are important for sustaining collaboration.